2014
DOI: 10.1038/cdd.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

Perforin oligomers form arcs in cellular membranes: a locus for intracellular delivery of granzymes

Abstract: Perforin-mediated cytotoxicity is an essential host defense, in which defects contribute to tumor development and pathogenic disorders including autoimmunity and autoinflammation. How perforin (PFN) facilitates intracellular delivery of pro-apoptotic and inflammatory granzymes across the bilayer of targets remains unresolved. Here we show that cellular susceptibility to granzyme B (GzmB) correlates with rapid PFN-induced phosphatidylserine externalization, suggesting that pores are formed at a protein-lipid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 42 publications
13
73
0
1
Order By: Relevance
“…5G). It has recently been reported that atomic force microscopy images of perforin indeed include a mixture of arcs and fully formed rings (45). The full rings have a mean diameter of 20 nm, which is similar to previous studies using EM (8,9,(23)(24)(25)(26)(27)45).…”
Section: Discussionsupporting
confidence: 87%
“…5G). It has recently been reported that atomic force microscopy images of perforin indeed include a mixture of arcs and fully formed rings (45). The full rings have a mean diameter of 20 nm, which is similar to previous studies using EM (8,9,(23)(24)(25)(26)(27)45).…”
Section: Discussionsupporting
confidence: 87%
“…According to this, increased flip-flop of lipids was observed in vesicles in the presence of cytolytic peptides such as gramicidin (Classen et al 1987), melittin (Rapson et al 2011), and magainin (Nguyen et al 2009). Transbilayer movement of lipids has been also shown for proteins like colicin E1 (Sobko et al 2004), Bax (Epand et al 2002(Epand et al , 2003, actinoporins (Anderluh et al 2003;Valcarcel et al 2001), and perforin (Metkar et al 2015).…”
Section: Induction Of Membrane Curvature and Lipid Flip-flopmentioning
confidence: 87%
“…The pore presumably evolves via a toroidal structure (Color figure online) stable architecture in which amphipathic protein oligomers form an arc on one side of the pore and lipids located on the opposite side complete the toroidal structure. Pores formed by actinoporins are archetypal of ''matrix-type'' (Anderluh et al 2003;Valcarcel et al 2001), while MACPF/CDCs pores (like perforin and pneumolysin) represent the ''arc-type'' (Metkar et al 2015;Sonnen et al 2014). Direct evidences support the formation of pores by MACPF/CDCs oligomeric arcs (Fig.…”
Section: Lipids and Proteins Acting Together: The Protein-lipid Porementioning
confidence: 89%
See 1 more Smart Citation
“…Once bound, the neutral pH of the synapse facilitates Prf1 oligomerisation 5 into ring and arc-shaped pores 6,7 , which are required for the diffusion of granzymes into the cytoplasm of the target cell to initiate apoptosis 8 . Prf1 therefore sits at the apex of the signaling cascade that triggers apoptotic target cell death and immune defense by cytotoxic lymphocytes.…”
Section: Introductionmentioning
confidence: 99%